The effect of different cytokinins on chlorophyll content and morphological features of in vitro Nidularium ’Kertész Jubileum’ - Ördögh, M. (International Journal of Horticultural Science, 2015)
During in vitro multiplication of Nidularium ‘Kertész Jubileum’, 20 g/l sucrose, 5 g/l agar, 100 mg/l inositol, and different concentrations of benzyladenine (BA), benzyladenine-riboside (BAR), kinetin (KIN), meta-topolin (mT) were added to the MKC (Knudson, 1946) basal medium. Furthermore, 0.1 mg/l naphthaleneacetic acid was used to every medium. Number of shoots, length of leaves, number and length of roots, chlorophyll (a+b) content were examined and evaluated with Ropstat statistical software. As compared to the other cytokinin, significantly most shoots were obtained in the case of applying BA. Increasing of BA-concentration (as far as 2 mg/l) enhanced shoot number (from 10.92 to 19.26) but 4 mg/l BA resulted only 6.63 shoot. The less efficient cytokinin was KIN, in most cases no more than about 2 shoot was achieved. Regarding the length of leaves, the higher level of BA effected averagely the shorter leaves (from 24,46 to 7.31 mm). KIN effected significantly the longest leaves (43.4-61.29) in inverse proportion to the concentration. The same cytokinin resulted the most (and the longest) roots with the highest rooting percentages, but more KIN decreased the number and length of roots (from 7.95 to 4.4 and from 38.49 to 22.73 mm). There were no definite correlation between cytokinin concentration and chlorophyll (a+b) content, but the highest doses resulted decreasing (except of meta-topolin which leads to the lowest values). Summarizing, BAR effected the highest contents (mostly more than 1400 μg/g), particularly in the case of 1 mg/l (1807.3 μg/g).